Influence of bleaching and coloring on ethyl glucuronide content in human hair. Issue 1 (22nd June 2017) - Petzel‐Witt, Silvana; Pogoda, Werner; Wunder, Cora; Paulke, Alexander; Schubert‐Zsilavecz, Manfred; Toennes, Stefan W.
Abstract : Ethyl glucuronide (EtG) is increasingly used in forensic toxicology as a marker for alcohol use in analyses of hair samples, especially in abstinence control. Some cosmetic treatments are considered to markedly reduce the EtG content. In view of especially many women with coloured hair the present study was performed to further investigate the effect of a variety of colouring procedures (bleaching, tinting, permanent and semi‐permanent dyeing, henna) on the EtG content. Untreated hair samples ( n = 12, EtG 13.9–64.7 pg/mg) were re‐analyzed (gas chromatography‐ negative chemical ionization mass spectrometry, 0.8 pg/mg quantification limit) after different treatment procedures. A decrease of the EtG content of at least 10% occurred in every case. The reduction in comparison to the untreated hair was expectedly high for permanent dyeing and bleaching with 18.1% of the initial content (median, range 0.0–50.9%) and 18.4% (0.0–46.7%), respectively. For henna this was 38.3% (0.0–83.0%), for tinting 70.4% (29.0–90.8%), for semi‐permanent dyeing 41.9% (0.0–77.4%). With permanent hair dye the EtG content was decreased to below 7 pg/mg in 10 of 12 cases, in 3 cases even below the LOD (0.2 pg/mg). Surprisingly henna treatment without oxidative component had a marked influence, EtG was below 2 pg/mg in 2 of 12 samples. The study showed that all tested coloration procedures markedly affected the deposited EtG content. Even temporary or henna coloration may have a marked effect. The present data support the recommendation to exclude hair samples with colour manipulations for analysis on the EtG content as a precaution in alcohol abstinence programs. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Different hair colouring procedures were performed with 12 EtG positive hair samples, including treatment with henna. The expected marked reductions in EtG contents even below the LOD were found. Unexpectedly, treatment with henna also affected EtG content massively.